Inhibition of 10% Alpinia galanga and Alpinia purpurata rhizome extract on Candida albicans growth - Fakhrurrazi Fakhrurrazi; Rachmi Fanani Hakim; Cut Cahya (Dental Journal (Majalah Kedokteran Gigi), 2012)
Background: One of normal oral flora that found in human oral cavity is Candida albicans (C. albicans). The overgrowth of this species can lead to opportunistic infection known as candidiasis. Two natural plants, Alpinia galanga rhizome and Alpinia purpurata rhizome, are natural remedies containing flavonoid, saponin, tannin, and triterpenoid used as antifungal component. Purpose: This experimental laboratory study is aimed to determine the inhibition of Alpinia galanga rhizome and Apinia purpurata rhizome on the growth of C. albicans. Methods: Alpinia galanga rhizome and Alpinia purpurata rhizome were extracted in ethanol solvent using soxhletation method. The ratio test was conducted on those two extracts at the concentration of 10% toward the growth of C. albicans through agar diffusion method. Results: The results showed that 10% Alpinia galanga rhizome extract and 10% Alpinia purpurata rhizome extract were able to inhibit the growth of C. albicans, about 7.33 mm for Alpinia galanga rhizome extract and 6 mm for Alpinia purpurata rhizome extract. The results of statistical tests using independent samples t-test showed that there was no significant difference between the inhibition of 10% Alpinia galanga rhizome extract and that of 10% Alpinia purpurata rhizome extract. Conclusion: In conclusion 10% Alpinia galanga rhizome extract and 10% Alpinia purpurata rhizome extract have weak inhibition on C. albicans growth.Latar belakang: Candida albicans (C. albicans) merupakan flora normal yang terdapat dalam rongga mulut, jika keseimbangannya terganggu maka jamur tersebut akan menjadi patogen dan dapat menyebabkan infeksi dalam rongga mulut yaitu kandidiasis. Lengkuas rimpang putih maupun lengkuas rimpang merah merupakan tanaman yang mengandung senyawa antijamur berupa flavonoid, saponin, tanin, dan triterpenoid. Tujuan: Penelitian eksperimental laboratoris ini dilakukan untuk mengetahui perbandingan daya hambat ekstrak lengkuas rimpang putih (Alpinia galanga) dengan ekstrak lengkuas rimpang merah (Alpinia purpurata) terhadap pertumbuhan C. albicans. Metode: Ekstrak lengkuas rimpang putih maupun lengkuas rimpang merah diperoleh dengan metode soxhletasi. Dilakukan pengujian perbandingan kedua ekstrak pada konsentrasi 10% terhadap pertumbuhan C. albicans dengan menggunakan metode difusi agar. Hasil: Ekstrak lengkuas rimpang putih 10% dan ekstrak rimpang lengkuas merah 10% mampu menghambat pertumbuhan C. albicans dengan daya hambat rata 7,33 mm untuk ekstrak lengkuas rimpang putih dan 6 mm untuk ekstrak lengkuas rimpang merah 10%. Hasil uji statistik menggunakan independent sampel t test menunjukkan tidak ada perbedaan bermakna antara respon hambat ekstrak lengkuas rimpang putih dan ekstrak lengkuas rimpang merah. Kesimpulan: Dari hasil penelitian ini dapat disimpulkan bahwa ekstrak lengkuas rimpang putih 10% dan ekstrak lengkuas rimpang merah 10% memiliki daya hambat yang lemah terhadap pertumbuhan C. albicans.